Research of independent DC electric field sensor with wireless power supply circuit. Issue 16 (17th December 2018) - When, Jianzhong; Yu, Zhanqing; Zhang, Chao; Mou, Ya; Huang, Yaosheng; Zhen, Zhiming
Abstract : The DC electric field strength is an important electromagnetic environment parameter of the high‐voltage direct current (HVDC) transmission line. Measurement results of the space electric field are dramatically affected by the size and the potential of the sensor. In addition, the battery‐powered solution of electric field sensor (EFS) is not feasible, for the reason that in the high‐voltage electric field environment, the replacement of the battery will bring security risks to the power system and workers. The wireless energy supply solution not only solves the problem of potential isolation of the sensor, but also ensures that the sensor can work continuously. Various wireless power transmission systems (WPTSs) were compared. Microwave wireless power transmission system (MWPTS) was selected as the power supply of EFS. The key boundary conditions of MWPTS were determined. Two microstrip receiving antennas were designed in this article. A good performance antenna with high permittivity substrate was designed, realising 4.26 dB gain with the area of 1 cm 2 at 5.8 GHz. The antenna meets the energy requirements of the EFS which is 10 m far from the source.